Objective Evaluation of Relationship Between Tear Film Stability and Visual Fatigue - Watanabe M; Hirota M; Takigawa R; Kato K; Ikeda Y (Clinical Optometry, 2025)
Maki Watanabe,1 Masakazu Hirota,2– 5 Ryusei Takigawa,2 Kanako Kato,2 Yuka Ikeda2 1Division of Orthoptics, Graduate School of Medical Care and Technology, Teikyo University, Itabashi-ku, Tokyo, Japan; 2Department of Orthoptics, Faculty of Medical Technology, Teikyo University, Itabashi-ku, Tokyo, Japan; 3Department of Ophthalmology, School of Medicine, Teikyo University, Itabashi-ku, Tokyo, Japan; 4Graduate Degree Program of Health Data Science, Teikyo University, Itabashi-ku, Tokyo, Japan; 5Graduate Degree Program of Comprehensive Applied Data Science, Teikyo University, Itabashi-ku, Tokyo, JapanCorrespondence: Masakazu Hirota, Department of Orthoptics, Faculty of Medical Technology, Teikyo University, 2-11-1 Kaga, Itabashi-ku, Tokyo, 173-8605, Japan, Tel +81-03-3964-1328, Fax +81-03-3963-0303, Email hirota.ortho@med.teikyo-u.ac.jpPurpose: To investigate the relationship between tear film stability and visual fatigue using two objective measurements: the non-invasive tear film break-up time (NI-BUT) and the binocular fusion maintenance (BFM) test.Methods: Eleven young adult volunteers (age [mean ± standard deviation], 20.7 ± 1.4 years) participated in this study. The NI-BUT was determined using the distortion of the mire ring. BFM was assessed by measuring the transmittance of liquid crystals placed in front of the subject’s non-dominant eye when binocular fusion was broken, and non-dominant eye was shifted to heterophoric. The volunteers were administered the NI-BUT and BFM before and after a 30-minute visual task.Results: NI-BUT (pre vs post: 9.12 ± 1.00 s vs 5.69 ± 3.11 s) was significantly shorter in the post-visual task than in the pre-visual task (P = 0.011). BFM (0.95 ± 0.09 vs 0.75 ± 0.16) was significantly lower in the post-visual task than in the pre-visual task (P = 0.012). The change in NI-BUT was significantly and positively correlated with the change in BFM (R2 = 0.385, P = 0.042).Conclusion: These objective findings support the association between tear film stability and visual fatigue.Plain Language Summary: Although subjective questionnaire studies have reported that eye dryness is associated with increased eye fatigue, objective evidence remains insufficient. In this study, we investigated the relationship between eye dryness and eye fatigue using objective measurements and found a correlation between them. These findings strengthen previous research and suggest the importance of preventing eye fatigue by maintaining proper tear film stability.Keywords: eye movements, binocular fusion, binocular vision, tear film, visual fatigue